Izvajanje določil pravilnika o izdaji dovoljenja za vzajemno katalogizacijo v sistemu COBISS.SI - Seljak, Marta (Organizacija znanja, 2006)
The article presents the way in which bibliographic information quality is assured within the COBISS.SI shared cataloguing. A special emphasis has been given on the activities related to the implementation of th provisions of the Rules on Issuing the Permission for Shared Cataloguing. The paper provides factual data illustrating these activities after the adoption of the Rules, and the terms and conditions to be met in relation to the registers within COBISS.
Keywords: bibliografske podatkovne zbirke; COBISS; COBISS.net; licence; pravilniki; Slovenia; Slovenija; vzajemna katalogizacija; zagotavljanje kakovosti